2014
DOI: 10.3889/oamjms.2014.023
|View full text |Cite
|
Sign up to set email alerts
|

A Toxic Hepatitis Caused the Kombucha Tea – Case Report

Abstract: Background: Toxic hepatitis may clinically manifest as other diseases of the liver, where it must always be considered in differential diagnoses of unexplained liver damage, such as poisoning with kombucha tea.Case report: 47-year old female patient was hospitalized and has consumed daily ounces of kombucha tea. During hospitalization patient was diagnosed with toxic hepatitis and treated with intravenous solutions of hepatic protective and ursodeoxycholic-acid (effective therapy). Conclusion: Examinations sho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 10 publications
0
8
0
1
Order By: Relevance
“…The case reports an etiological association of all four patients since all of them Journal of Chemistry had consumed Kombucha tea in proximity to the onset of symptoms and their subsequent disappearance after cessation of drinking the beverage [55]. Some individuals have reported that they felt dizziness and nausea after consumption of Kombucha tea [56]. However, it was not explained whether these symptoms are a result of unusual toxins developed in a particular batch of Kombucha tea.…”
Section: Safety Issues and Controlling Potential Hazards Of Kombuchamentioning
confidence: 99%
See 1 more Smart Citation
“…The case reports an etiological association of all four patients since all of them Journal of Chemistry had consumed Kombucha tea in proximity to the onset of symptoms and their subsequent disappearance after cessation of drinking the beverage [55]. Some individuals have reported that they felt dizziness and nausea after consumption of Kombucha tea [56]. However, it was not explained whether these symptoms are a result of unusual toxins developed in a particular batch of Kombucha tea.…”
Section: Safety Issues and Controlling Potential Hazards Of Kombuchamentioning
confidence: 99%
“…In addition to acetic acid, Kombucha tea contains several organic acids [6,33]. Some of these metabolites have the potential to damage liver and kidney at high concentrations, as evident by few case reports [56,59,60]. Kombucha tea is contraindicated in pregnant and lactating women [53].…”
Section: Safety Issues and Controlling Potential Hazards Of Kombuchamentioning
confidence: 99%
“…It comes from aerosol and certain refrigerants production and can cause adverse health effect and hepatic toxicity if recommended dose is exceeded (Agency for Toxic Substances and Disease Registry [ATSDR], 2005;Kovacevic et al, 2014). Four HIV positive patients reported secondary effects related to its consumption, such as allergic reaction, ictericia, nausea, vomit, neck pain and headache.…”
Section: Contraindications Of Kombuchamentioning
confidence: 99%
“…It is extremely important to use sanitized utensils and work in clean areas while making kombucha, in order to have control over the growth of microorganisms and to prevent unwanted contamination (Watawana et al, 2015). Likewise, it is important to control pH levels during fermentation of kombucha, and preferably stop this process when a pH level of 4.2 is reached, since the overproduction of acetic acid may be counterproductive (Kovacevic et al, 2014). Other food safety methods include pasteurizing the final product to prevent overproduction of alcohol and carbon dioxide, as well as the addition of 0.1% of sodium benzoate and 0.1% of potassium sorbate as food preservatives, and finally, keeping it refrigerated (Watawana et al, 2015).…”
Section: Preparation Of Kombuchamentioning
confidence: 99%
“…Taze kaynatılmış su kullanılarak (1 litre) ve 50-200 g/L oranında sakkaroz (çay şekeri) ile tatlandırıldıktan sonra, çoğunlukla siyah çay yapraklarıyla (1.5-5.0 g/L) demlenen Kombu çayı (10 dakika); yapraklar uzaklaştırıldıktan sonra, oda sıcaklığına soğutulmakta ve ardından bakteri ve mayaların simbiyotik kültürü (SCOBY, Kombu çayı mantarı) ve daha önce fermente edilmiş çaydan (100-150 mL/L) eklenerek, üzeri temiz bir bezle örtüldükten sonra fermentasyona bırakılmaktadır (7-60 gün) [5,7,11,20,[24][25]32]. Süre ve sıcaklık artışına bağlı olarak artan asetik asidin olumsuz etki yaratmaması için fermentasyonun; pH 4.2'ye ulaştığında sonlandırılması, alkol ve CO2 oluşumunu kontrol edebilmek için ise ürünün pastörize edilmesi veya koruyucu (%0.1 sodyum benzoat ve %0.1 potasyum sorbat) ilave edilip soğukta muhafaza edilmesi önerilebilmektedir [24,25,34].…”
Section: Introductionunclassified